PDMS-urethanesil hybrid multifunctional materials: combining CO2 use and sol–gel processing - Günther, Florian; Lima, Elton F. S.; Rossi de Aguiar, Kelen M. F.; Bearzi, Jefferson R.; Simões, Mateus B.; Schneider, Ricardo; Bini, Rafael A.; Ribeiro, Sidney J. L. [UNESP]; Man, Michel Wong Chi; Rischka, Klaus; Aguiar, Flávio H. B.; Pereira, Renata; et al. (Springer Nature, 2020)
CO2 mitigation by cycloaddition to bis-epoxides to obtain bis-cyclocarbonates (CC) paved one way to a new class of polyurethanes (PUs), the non-isocyanate polyurethanes (NIPUs). By using molecules functionalized with alkoxysilyl groups as end chain it is possible to obtain hybrid NIPUs, also called urethanesils, by sol–gel chemistry. Using bis-cyclocarbonate polydimethylsiloxane (CCPDMS) with proper diamines and end-chain amino silanes followed by sol–gel processing leads to versatile hybrid non-isocyanate polydimethylsiloxane urethanes (PDMS-urethanesil). This review reports—besides our recent studies about PDMS-urethanesil materials—the sol–gel chemistry applied to synthesize urethanesil and its applications. While the antimicrobial, photochromic, and anticorrosion properties of urethanesil loaded with phosphotungstic acid as well as the luminescent effect of material loaded with Eu3+ have already been reported, antimicrobial features of urethanesil loaded with phosphoric acid are our newest findings which we herein report for the first time. The impact of the inorganic acid used on the sol–gel process is highlighted together with the importance of antibiofouling properties. Although the antibiofouling mechanism is still under investigation, the broad spectrum of action of phosphoric acid-loaded urethanesil is worth mentioning, since it has been tested to be efficient against some pathogenic bacteria including a drug resistant Staphylococcus aureus strain as well as pathogenic fungi and yeast. Due to the simple, straightforward, and highly reproducible synthesis as well as the opportunity to obtain versatile materials with tuneable mechanical and physical properties, this new class of hybrid materials promises to be applicable in different industrial fields. [Figure not available: see fulltext.].
Keywords: Anticorrosion; Biomedical coatings; Inorganic–organic hybrid; Non-isocyanate polyurethanes; Photonic; Polydimethylsiloxane